(untitled) (Jurnal Destinasi Pariwisata, 2025)
A tourism village rich in customary heritage and traditional crafts faces challenges in educating tourists without compromising the sacred value of its culture. This research aims to explore the education and marketing strategies used by Tenganan Pegringsingan tourism village in promoting its customs and traditional crafts without reducing the inherent sacred values. This case study focuses on an education-based marketing approach in the tourism village, emphasizing the importance of preserving cultural sacredness amidst tourism market demands. The research employs a qualitative-descriptive approach through in-depth interviews, field observations, and document analysis, including a study of lontar (palm-leaf manuscripts) that govern customary law and sacred values within the community. The results indicate that the main challenges faced by Tenganan Pegringsingan tourism village include cultural commercialization, tourists’ lack of knowledge about sacred values, and the influence of modernization. To overcome these, the village implements strategies such as developing edutourism that explains the meaning behind the customs and crafts, restricting tourist access to sacred areas, and sacredness-based marketing that emphasizes cultural values. These strategies demonstrate that the tourism village can utilize tourism as a means of education, allowing tourists not only to view the customs and crafts as commodities but also to understand the noble values behind them. This research is expected to provide insights for other tourism villages in managing the sustainable marketing of their customs and crafts without losing their sacred values.